The Role of School Committee Management in Improving Student Discipline During the Covid-19 Period at MTsN 6 Tanah Datar - Wiwit Vianora; Sufyarma Marsidin; Suswati Hendriani (al-fikrah: Jurnal Manajemen Pendidikan, 2021)
The discussion of this article will analyze and describe the role of school committee administrators as a consideration body, a support agency, as a controlling body and as a mediator body, in improving the quality of education during the covid-19 pandemic. The role of the school committee management is very large and has a lot of benefits for increasing student discipline in learning. The method of this article uses a descriptive qualitative approach that seeks to understand the various concepts found in the research process. This research method uses descriptive qualitative research by placing procedures or scientific methods to obtain data with a specific purpose. This study uses observation, documentation, and interviews to obtain conditions for the object to be studied. with this discussion are the types and sources of secondary data that will be used in finding the results of this discussion. The results of this study indicate that the school committee management at MTsN 6 Tanah Datar has a very important role in efforts to improve student discipline during this Covid-19 period. Furthermore, the efforts made by the school committee management in improving discipline during the COVID-19 pandemic can be seen in their involvement in efforts to participate in decision making. Meanwhile, the obstacles they face during this pandemic are the parents' lack of awareness of their children about children's education, especially since learning is currently in the form of online/on-line. Fostering good relations and cooperation between school committee administrators and parents/guardians is a solution taken by school committee administrators in improving student learning discipline.